The Morning: Constructing Moral Space from the African American Experience in Bioethics - Carter, Donald; Simpson, Kara; Reaves, Alvin (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Bioethicists, globally, have historically enjoyed collaborative exchange and relationships. However, given the current political strain, moral deliberation is threatened and diminished. The redevelopment of morally safe spaces and the pursuit of truth require the embodiment of moral courage and intentionality. To meet the moment, bioethics must move beyond neutrality by drawing on the African American experience’s emphasis on moral clarity and community accountability — embracing positionality and centring marginalized voices to confront socio-political tensions within and beyond academia. The concepts of the 3Ms (moaning, mourning, and morning) provide a framework for creating a more inclusive moral space. Based in social work theoretical praxis, Moaning refers to African American pain and suffering, Mourning, the collective effort to overcome grief, and Morning, the representation of breakthrough and transformation from hardships. Despite the three concepts being a powerful exploration of the African American tradition, it can be helpful to others outside this community. This essay focuses, however, only on the concept of “Morning” — a metaphor that serves as a blueprint for the bioethics profession to address the current political climate. It is imperative that bioethics elevate the voices and listen to the past experiences of the marginalized and oppressed. These experiences can provide a blueprint for transcending barriers of social and political inequities, both domestically and abroad. We suggest reevaluating the use of neutrality, opting instead for clear commitments to positions on ethical dilemmas.